Regional citrate-calcium anticoagulation during polymyxin-B hemoperfusion: A case series - Forfori, Francesco (Int J Artif Organs, 2018)
INTRODUCTION: So far, only heparin-based anticoagulation has been proposed during polymyxin-B hemoperfusion. However, postsurgical septic patients can be at high risk of bleeding due to either surgical complications or septic coagulation derangement. Consequently, heparin should not represent in some cases the anticoagulation regimen of choice in this type of patients. METHODS AND RESULTS: We present a case series of four postsurgical septic patients treated with polymyxin-B hemoperfusion using regional citrate anticoagulation. All the treatments were performed without complications. During each treatment, there were no episodes of filter clotting, no bleeding, and no metabolic complications for any of the patients. CONCLUSION: To our knowledge, this is the second published report on the use of citrate anticoagulation during polymyxin-B hemoperfusion. Our case series continued to show that regional citrate anticoagulation regimen is feasible and safe during polymyxin-B hemoperfusion treatment in postsurgical septic patients.